2008
DOI: 10.1182/blood-2008-03-146290
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid dendritic cells efficiently cross-prime naive T cells in vivo after TLR activation

Abstract: Cross-presentation is a crucial mechanism in tumoral and microbial immunity because it allows internalized cell associated or exogenous antigens (Ags) to be delivered into the major histocompatibility complex I pathway. This pathway is important for the development of CD8 ؉ T-cell responses and for the induction of tolerance. In mice, cross-presentation is considered to be a unique property of CD8␣ ؉ conventional dendritic cells (DCs). Here we show that splenic plasmacytoid IntroductionCross-presentation is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
136
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(146 citation statements)
references
References 58 publications
7
136
2
1
Order By: Relevance
“…This is profound, considering the important role type I IFNs play in regulating adaptive immunity to a number of other viral infections and, of particular note here, the dsDNA viruses VV and adenovirus (AdV5), which lack the ability to elicit an adaptive immune response in the absence of type I IFNs (61,62). We therefore propose that the main role of pDCs here is not to provide type I IFNs but to act as antigen-presenting cells (APCs) (13), a property recently shown to involve ligation of TLR7 and TLR9 (35), which are, coincidently, the two same TLRs that we have found to be responsible for innate recognition of FPV (E. L. Lousberg, submitted for publication). In antigen presentation experiments which involved the proliferation of OT-I T cells in vitro and in vivo, we demonstrated that pDCs had an important role in antigen presentation and were in fact responsible for presenting antigen to a significantly greater extent than cDCs when DCs were harvested from a previously immunized mouse and coincubated with OT-I T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is profound, considering the important role type I IFNs play in regulating adaptive immunity to a number of other viral infections and, of particular note here, the dsDNA viruses VV and adenovirus (AdV5), which lack the ability to elicit an adaptive immune response in the absence of type I IFNs (61,62). We therefore propose that the main role of pDCs here is not to provide type I IFNs but to act as antigen-presenting cells (APCs) (13), a property recently shown to involve ligation of TLR7 and TLR9 (35), which are, coincidently, the two same TLRs that we have found to be responsible for innate recognition of FPV (E. L. Lousberg, submitted for publication). In antigen presentation experiments which involved the proliferation of OT-I T cells in vitro and in vivo, we demonstrated that pDCs had an important role in antigen presentation and were in fact responsible for presenting antigen to a significantly greater extent than cDCs when DCs were harvested from a previously immunized mouse and coincubated with OT-I T cells.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that pDCs are essential for the induction of a cytolytic response directed against an FPV-expressed antigen (11); however, the results from our current study suggest that this effect did not lie in the capacity of pDCs to secrete large amounts of type I IFNs, as originally postulated, as here we clearly show that they appear to make no contribution to the induction of adaptive immune responses to recombinant FPV. Recent reports have indicated that pDCs can also present antigens and therefore contribute directly to the development of adaptive immune responses (35,55). With this in mind, we sought to determine whether the crucial role of pDCs in the formation of anti-FPV adaptive immunity may lie in their antigen presentation functions.…”
Section: Type I Ifn Receptor Expression Does Not Affect Fpv-mediated mentioning
confidence: 99%
“…DQ-OVA is a self-quenched conjugate of OVA that exhibits green fluorescence after proteolysis and red fluorescence when the fragments accumulate in organelles at high concentrations (31,32). After 20 min incubation, the percentage of DC having degraded DQ-OVA (green fluorescence) was lower when DC were pretreated with CpG compared with untreated DC, although both populations had captured DQ-OVA as revealed by pulse-chase experiments (Fig.…”
Section: Use Of Different Ag Entry Routes For Cross-presentation By Fmentioning
confidence: 99%
“…DQ-OVA (Invitrogen) is a self-quenched dye conjugate of OVA that exhibits green fluorescence upon degradation and red fluorescence when it accumulates in organelles at high concentration (31,32). Flt3l DC were incubated for the indicated times with DQ-OVA (10 mg/ml) at 37˚C or at 4˚C in the presence of 0.1% azide and were stained with anti-CD11c Abs and analyzed by flow cytometry (Canto flow cytometer; BD Biosciences).…”
Section: Endocytosis Assaymentioning
confidence: 99%
“…However, these two DC functions are not so strictly compartmentalized. Indeed, although less efficient than cDCs, TLR-or virus-licensed pDCs are able to cross-present particulate Ags and to cross-prime naive CD8 T cells (11). Moreover, there is growing evidence that pDCs are dispensable for IFN-I responses to certain viruses, suggesting that other cells must be involved in the production of IFNs-I.…”
mentioning
confidence: 99%